2007
DOI: 10.1017/s0022029907002476
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the antibody isotype response in serum and milk of heifers vaccinated with a Staphylococcus aureus bacterin (LysiginTM)

Abstract: The objective was to characterize the antibody isotype responses to vaccination with a commercial Staphylococcus aureus bacterin in dairy heifers. Twenty-five Holstein-Friesian dairy heifers were assigned at random to one of two groups, vaccinates (n=14) or controls (n=11). Vaccinates received two 5-ml doses of Lysigin 28 d apart in late gestation. Both groups were challenged with a heterologous serotype 5 strain of Staph. aureus by aseptic intramammary infusion on days 6, 7 and 8 of lactation. Samples for ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Efficacy of a vaccine refers to the reduction in disease measured in a carefully monitored, LUBY et al, 2007). Similar results were obtained in studies that used avirulent (PELLIGRINO et al, 2008) or inactivated S. aureus (TENHAGEN et al, 2001) vaccine formulations or vaccines including insoluble bacterial fragments of two field S. aureus field strains and secreted antigens of a third field strain (LEITNER et al, 2013).…”
Section: What Is Vaccine Efficacy?mentioning
confidence: 65%
“…Efficacy of a vaccine refers to the reduction in disease measured in a carefully monitored, LUBY et al, 2007). Similar results were obtained in studies that used avirulent (PELLIGRINO et al, 2008) or inactivated S. aureus (TENHAGEN et al, 2001) vaccine formulations or vaccines including insoluble bacterial fragments of two field S. aureus field strains and secreted antigens of a third field strain (LEITNER et al, 2013).…”
Section: What Is Vaccine Efficacy?mentioning
confidence: 65%
“…This correlates well with our results, because significant differences in antibody titres between vaccinated and non-vaccinated groups were observed only after the administration of the third dose of the vaccine. On the other hand, in another work with the same Lysigin TM vaccine, anti-S. aureus antibody levels in milk were not different from control animals suggesting that vaccination provided minimal immune protection (Luby et al 2007). Finally, Prenafeta et al (2010) evaluated a new commercial vaccine produced in Spain (Startvac, HIPRA Laboratories) based on extracellular slime associated antigenic complex (SAAC) from S. aureus.…”
Section: Discussionmentioning
confidence: 99%
“…Lysigin® is claimed for reducing new IMI caused by S. aureus, and coagulase-negative Staphylococcus ​species (CNS) provided that vaccination program starts on heifers at an early age of 6 months with booster vaccination every six months until calving (Nickerson et al., 1999). However, in other studies it was shown that Lysigin® vaccinated cows were not protected from new IMI, had no significant increase in antibody titers in milk and had no significant reduction in somatic cell count (SCC) as compared to non-vaccinated control cows (Luby et al., 2007; Middleton et al., 2009; Middleton et al., 2006). S. aureus is highly adaptive and often resistant to antimicrobial treatment and host defense systems (Lozano et al., 2016; Monecke et al., 2016; Proctor et al., 2014), and thus threatens human and animal health by turning into a multidrug-resistant pathogen (Fitzgerald, 2012a; 2012b; Holmes and Zadoks, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…It results in the massive use of antimicrobials as dry cow therapy (DCT) for prophylactic control as well as for treatment of cases of mastitis (Barkema et al., 2006; Brady et al., 2006; Sanchez et al., 1994). Currently, available bacterin-based vaccines (Lysigin® and Startvac®) are ineffective for the prevention of mastitis caused by S. aureus (Bradley et al., 2015; Luby et al., 2007; Middleton et al., 2009; Middleton et al., 2006; Schukken et al., 2014). In the USA, Lysigin®, a Bacterin made of five strains is used as a vaccine against S. aureus intramammary infection (IMI) (Ma et al., 2004).…”
Section: Introductionmentioning
confidence: 99%